THEORETICAL AND PRACTICAL FOUNDATIONS FOR THE DEVELOPMENT OF THE FOOD INDUSTRY ENVIRONMENTAL PROBLEM - Tleuov Nietulla Rakhmanovich (EPRA International Journal of Research and Development (IJRD), 2023)
The article proposes the theoretical and practical foundations for the development of the food industry, taking into account the environmental problem.